Notes on the rules governing the trial in Iraqi criminal legislation A comparative study - Xalind, Kawther Ahmed; Smail, Muhammed Kakalah (Journal of Legal and Political Studies, 2024)
There are several amendments to the Iraqi Criminal Procedure Law No. (23) for the year 1971, but the aforementioned law is not without shortcomings and shortcomings, which makes it a subject of consideration and observation among scholars, researchers and specialists in this field and their criticisms, which is either a lack of words or words in the formulation Some of its articles, or in the non-organization of some issues that must be organized explicit text, in view of the development of science and the advancement of technology, or not to classify some materials in the right place for them, and scattered here and there. There are also procedural rules contained in the Penal law, while the place of these rules is the law of Criminal Procedure, which led us to study this law and make observations on it, as well as observations made by other researchers. In order to avoid these shortcomings and shortcomings when making amendments to it. Key Words: Ambiguity of text, conflict of jurisdiction, criminal court, trial stage, judge’s authority
Keywords: Ambiguity of text; conflict of jurisdiction; criminal court; trial stage; judges authority